PHARMACOTHERAPY IN PATIENTS WITH ERECTILE DYSFUNCTION AND BENIGN PROSTATIC HYPERPLASIA IN THE ABSENCE OF RISK OF DISEASE PROGRESSION - A. A. Kamalov; A. M. Tahirzade (Исследования и практика в медицине)
Purpose. Evaluation of the effectiveness and safety of various pharmacotherapy options in patients with erectile dysfunction (ED) in combination with benign prostatic hyperplasia (BPH).Materials and methods. In 127 men with BPH and ED, pharmacotherapy was performed for 3–12 months. Inclusion criteria: IPSS ≥8 points, IIEF-5 ≤21 points, prostate volume ≤40 cm3, prostatic specific antigen (PSA) level <1.5 ng/ml. In patients who are interested in improving erectile function, the following treatment options have been performed: monotherapy with tamsulosin 0.4 mg daily (n = 30), sildenafil monotherapy 25 mg daily (n = 31), tamsulosin 0.4 mg daily and sildenafil 25 mg daily (n = 34).Results. With combined therapy, statistically significant and most pronounced improvement occurred at all time points for all 5 parameters: IPSS, QoL, IIEF-5, maximum urination rate (Qmax), residual urine volume. Monotherapy with α1-adrenoblocker at all times led to a significant improvement in 4 parameters (IPSS, QoL, Qmax, residual urine volume), but had no effect on erectile function. Monotherapy with a phosphodiesterase type 5 inhibitor (PDE-5) improved IIEF-5 from the very beginning, and the remaining parameters (IPSS, QoL, Qmax, residual urine volume) after 6 months.Conclusions. The combination of α1-adrenoblocker and PDE-5 inhibitor can be considered as an optimal treatment option in patients with LUTS and ED with prostate volume <40 cm3 and PSA level <1.5 ng/ml.